Pengaruh Kemampuan Pemahaman Konsep, Kemampuan Komunikasi dan Koneksi Terhadap Kemampuan Pemecahan Masalah - Hartati, Sri; Abdullah, Ilham; Haji, Saleh (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2017)
This research aims to determine the influence of concept understanding ability (X1), communication ability (X2) and mathematical connection ability (X3) on problems solving ability (Y); the influence of concept understanding ability (X1) on communication ability (X2); the influence of concept understanding ability (X1) on mathematical connection ability (X3); and communication ability (X2) on connection ability (X3). This research is a survey research with quantitative approach. Population of the research is the students of second grade Public Junior High School 1 of Padang Jaya. The sample is taken by using non-probability sampling method using saturated sampling. Data is analyzed by using Path Analysis with 5% significance level. The research result shows that (1) concept understanding ability (ρyx1X1 = 0,374), communication ability (ρyx2X2 = 0,181 and connection ability (ρyx3X3 = 0,201) give influence on problems solving ability; (2) the concept understanding ability (ρx2x1X1= 0,323) gives influence on communication ability; (3) concept understanding ability (ρx3x1X3 = 0,442) gives influence on connection ability and (4) communication ability (ρx3x2X3 = 0,470) give influence on connection ability.